Unleashing Job Loyalty through Leadership, Commitment, and Motivation: Melepaskan Loyalitas Kerja melalui Kepemimpinan, Komitmen, dan Motivasi - Yunanto Bagas Surya Panigoro; vera firdaus (Academia Open, 2024)
This quantitative study examines the impact of leadership, commitment, and work motivation on work loyalty among employees of PT. Benelli Perkasa Motor. Using a total sampling technique, data were collected from 105 employees through distributed questionnaires and analyzed using SPSS. Results indicate that effective leadership, employee commitment, and high work motivation positively influence work loyalty. The findings underscore the importance of fostering these factors to reduce turnover rates, enhance productivity, and cultivate a positive work environment within the organization. Highlight: Leadership influences work loyalty positively. Employee commitment drives organizational success. High motivation boosts productivity effectively. Keyword: Leadership, Commitment, Work Motivation, Work Loyalty, PT. Benelli Perkasa Motor